Taking Stock, July 2015 : An Update on Vietnam's Recent Economic Developments - World Bank (Hanoi, 2015)
Economic activity continued to firm up in 2015, driven by domestic demand. After coming in at 6 percent in 2014, GDP growth accelerated to 6.28 percent during the first half of 2015, the fastest first-half-of-the-year growth rate in the past five years. The recovery was driven by strong activity in manufacturing and construction, which together contributed nearly half of overall GDP growth. Retail sales also performed strongly, posting 8.3 percent (in real terms) in the first six months of 2015, up from 6.3 percent in 2014. However, despite the pickup in retail activity, overall services (which account for nearly 40 percent of GDP) rose modestly at 5.9 percent in the first half of 2015. In part, this reflected a struggling tourism sector, with tourist visits in the first six months down by 11 percent year-on-year. On the demand side, stronger growth was driven by investment (spurred by strong FDI inflows) and stronger private consumption boosted by low inflation. The contribution of net exports turned negative as sluggish external demand weighed on export growth while strengthened domestic activity continued to fuel import growth.